Characterization of maize (Zea mays L.) Wee1 and its activity in developing endosperm - Sun, Yuejin (The National Academy of Sciences, 1999)
We report the characterization of a maize Wee1 homologue and its expression in developing endosperm. Using a 0.8-kb cDNA from an expressed sequence tag project, we isolated a 1.6-kb cDNA (ZmWee1), which encodes a protein of 403 aa with a calculated molecular size of 45.6 kDa. The deduced amino acid sequence shows 50% identity to the protein kinase domain of human Wee1. Overexpression of ZmWee1 in Schizosaccharomyces pombe inhibited cell division and caused the cells to enlarge significantly. Recombinant ZmWee1 obtained from Escherichia coli is able to inhibit the activity of p13(suc1)-adsorbed cyclin-dependent kinase from maize. ZmWee1 is encoded by a single gene at a locus on the long arm of chromosome 4. RNA gel blots showed the ZmWee1 transcript is about 2.4 kb in length and that its abundance reaches a maximum 15 days after pollination in endosperm tissue. High levels of expression of ZmWee1 at this stage of endosperm development imply that ZmWee1 plays a role in endoreduplication. Our results show that control of cyclin-dependent kinase activity by Wee1 is conserved among eukaryotes, from fungi to animals and plants.